Bioprocessing Of Agro-Waste And Organic Domestic Waste For Broiler Feeds - Ibrahim, Suhaidah (2014)
This study has focused mainly on the selection of potential degrading isolates, development of powder inoculum for decomposition of food waste, development of home decomposing prototype system as well as the potential of decomposed material as poultry feed. A total of 23 types of microorganisms were successfully isolated from two sources; composted agro waste and fermented food waste. In the potential screening study, a mixed culture inoculum consisting of isolate H1, H4, C and E was able to degrade 100.00 g of substrate within 10 to 11 days with highest crude protein and crude lipid contents of 72.97 ± 1.59 % and 29.09 ± 1.67 %, respectively, after 9 days of bioprocessing. Isolate H1, H4, C and E were identified to be Pseudomonas pseudoalcaligenes H1, Pseudomonas stuzerii H4, Serratia plymuthica C, and Bacillus macerans E.